Detection of high molecular weight dsRNA persisting in Dianthus species - Szegő, Anita (Acta Biologica Szegediensis, 2005)
Cryptic plant viruses are seed-borne dsRNA-viruses, which co-exist life-long with the host plant, without inducing any apparent symptoms. Since growth conditions and the hostvirus combination (cultivar, strain, isolate, thermotherapy, etc.) are known to influence virus multiplication, we wanted to find out what effect long-term tissue culturing has on the survival of carnation cryptic virus (CarCV). 21 members of Hungarian Dianthus germplasm collection have been aseptically grown for 16 years. Total nucleic acids of these Dianthus species and of Silene vulgaris were separated by non-denaturing gel electrophoresis and the dsRNA-pattern was visualized by immunoblotting using dsRNA-specific monoclonal antibodies. Genomic dsRNAs of CarCV were detected in D. caryophyllus. In four additional species: D. superbus, D. giganteus D. gratianapolitanus and Silene vulgaris several dsRNA-species in the same size range as the genomic dsRNAs of CarCV were detected. We also show that three other cryptoviruses, the beet cryptic viruses BCV1, -2 and –3 can persist under in vitro conditions. Our results indicate that cryptic viruses are so well adapted to their hosts that they can persist after more than a decade of in vitro culturing despite the dramatic change of the environment.